Clinical-pathological parameters in squamous cell carcinoma of the tongue - Dantas Dilana Duarte Lima; Ramos Carlos César Formiga; Costa Antonio de Lisboa Lopes; Souza Lélia Batista de; Pinto Leão Pereira (Fundação Odontológica de Ribeirão Preto, 2003)
The correlation between TNM classification and histological scores of malignancy, and the correlation of these parameters with the prognosis was evaluated in 16 cases of squamous cell carcinoma of the tongue. The cases were selected from the files of "Dr. Luiz Antônio" Cancer Hospital, Natal, RN, Brazil. After analysis of the patients' records, the data concerning TNM classification and prognosis (in a 5-year-follow-up) were obtained. All cases were classified according to the histological malignancy grading system proposed by Anneroth et al. (1) [Scand Dent Res 1987;95:229-249]. There was no correlation (r = 0.3083) between TNM classification and histological scores of malignancy. There was significant correlation (r = 0.7206) between TNM classification and prognosis, but there was no correlation between the histological scores of malignancy and the prognosis. It was concluded that TNM classification is an important prognostic indicator of squamous cell carcinoma of the tongue.